2017
DOI: 10.1186/s12974-017-0998-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Inhibiting the microglia activation improves the spatial memory and adult neurogenesis in rat hippocampus during 48 h of sleep deprivation

Abstract: BackgroundSleep deprivation (SD) leads to cognitive impairment. Neuroinflammation could be a significant contributing factor in the same. An increase in regional brain pro-inflammatory cytokines induces cognitive deficits, however, the magnitude of the effect under SD is not apparent. It is plausible that microglia activation could be involved in the SD-induced cognitive impairment by modulation of neuronal cell proliferation, differentiation, and brain-derived neuronal factor (BDNF) level. The present study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(177 citation statements)
references
References 48 publications
9
168
0
Order By: Relevance
“…For example, cytokines (especially HMGB1, NFκB, and TNFα [30]) secreted from circulating or fixed mononuclear cells regulated microglial feedback reactions [31], upregulating MCP-1 expression and inflammatory cascade signaling pathways and triggering neuroinflammation in the hippocampus [32]. In addition, microglial elimination or inhibition suppressed hippocampal inflammatory responses and reduced the levels of cytokines such as IL-6, IL-1β, and TNFα following anesthesia and other pathological conditions [17,33,34]. Moreover, the level of inositol 1,4,5-triphosphate type 2 receptor-dependent calcium was reduced in astrocytes, even after a sedative dose of anesthetic [35], and long-term inhibition of astrocytes is consistent with synaptic suppression and cognitive deficiencies [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cytokines (especially HMGB1, NFκB, and TNFα [30]) secreted from circulating or fixed mononuclear cells regulated microglial feedback reactions [31], upregulating MCP-1 expression and inflammatory cascade signaling pathways and triggering neuroinflammation in the hippocampus [32]. In addition, microglial elimination or inhibition suppressed hippocampal inflammatory responses and reduced the levels of cytokines such as IL-6, IL-1β, and TNFα following anesthesia and other pathological conditions [17,33,34]. Moreover, the level of inositol 1,4,5-triphosphate type 2 receptor-dependent calcium was reduced in astrocytes, even after a sedative dose of anesthetic [35], and long-term inhibition of astrocytes is consistent with synaptic suppression and cognitive deficiencies [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, microglia produce inflammatory cytokines to reduce the survival of newborn neurons after focal cerebral ischemia [26]. Inhibiting microglia activation improves spatial memory and adult neurogenesis in the rat hippocampus during 48 h of sleep deprivation [27]. Next, we investigated the function of microglia in neurogenesis after exposure to microgravity and found that the microglia were activated and the number of NSCs decreased strikingly in rat hippocampus after 7 d tail suspension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inflammatory factors can affect the function of synaptic connections. In a mouse model of sleep deprivation, an upsurge in inflammatory factors such as TNF-α, IL-1β and IL-6 derived from activated microglia was found in the dentate gyrus and CA2-3 areas of the hippocampus, which was coupled by a significant decline in spatial memory function [38]. IL-1β can reduce the expression of synaptophysin in presynaptic membrane and PSD-95 in postsynaptic of septic rats model, thereby reducing LTP [39,40] through MAPK pathway.…”
Section: Decreased Microglia Activation In Lps Treated α 2a -Ar Gene mentioning
confidence: 99%